Implementation of a chemotherapy stewardship process. (4th July 2020) - Hennes, Emily R; Reed, Michael; Mably, Mary; Jared, Jason; Bergsbaken, Jason J; Deming, Dustin; Callander, Natalie; O'Regan, Ruth
Abstract: Purpose: To design and implement a chemotherapy stewardship process to optimize the location of chemotherapy administration in an effort to decrease the number of inappropriate inpatient anticancer regimen administrations and decrease institutional costs associated with inpatient administration. Summary: As the costs of anticancer agents continue to rise, it is crucial that multidisciplinary efforts are aimed at managing anticancer medication utilization; this is especially important for high-cost medications, medications whose use requires increased monitoring due to safety concerns, and medications that do not exert effects quickly and, as such, can be more appropriately administered in the outpatient setting. It is imperative that pharmacists play a role in managing chemotherapy medication utilization, as pharmacists provide expertise in formulary management, a vast knowledge of financial impact and reimbursement processes, and clinical knowledge that can help predict the expected effectiveness and adverse effects of each anticancer regimen. Our institution sought to develop and implement a multidisciplinary chemotherapy stewardship program targeting the optimization of site of anticancer agent administration with a goal of decreasing both cost and inappropriate utilization of high-cost, high-risk anticancer agents. Conclusion: Implementation of a chemotherapy stewardship service may decrease the number of inappropriate inpatient anticancer regimen administrations and decrease inpatient resource use, thereby decreasing costs to institutions. The concept of a chemotherapy stewardship process was well received by multidisciplinary healthcare colleagues, and a collaborative approach should be used to design and implement such processes.